User Satisfaction Analysis of E-Samsat SUMUT Application Using End User Computing Satisfaction (EUCS) Approach - Naufal, M Farid; Utomo, Rio Guntur; Achmad, Kusuma Adi (ISB Atma Luhur, 2023)
Technological developments have continued to develop until now and the community has even made it a necessity, one of which is the motorized vehicle tax payment processing service, where payments can be made via e-banking or a predetermined Bank ATM. Because of this, users believe that there is little to no difference between traditional Samsat and E-Samsat, the user returns to the Samsat Office to obtain validation of vehicle registration certificates (STNK). User satisfaction is formulating user satisfaction and comparing expectations and reality as follows: if expectations reality then very satisfied, if expectations = reality then satisfied and If expectations reality then not satisfied. The purpose of this study is to find out what factors influence user satisfaction in the North Sumatra E-Samsat application and recommendations to application developers so that user satisfaction does not decrease. This study uses quantitative methodology. Quantitative is a research method in which data collection techniques are carried out through surveys and questionnaire instruments and data analysis is carried out statistically. This study will use the End User Computing Satisfaction method, the EUCS method was chosen because it has 5 variables of content, accuracy, format, ease of use, and timeliness to measure factors that influence user satisfaction from information systems. The results of the discussion from this study using the EUCS method each variable get a score of 4 (satisfied) out of 5 total scores. But it's not perfect yet, so some improvements are needed to further increase user satisfaction.